Molecular mechanism underlying quercetin induced apoptosis by insilico analysis and in prostate Cancer pc-3 cells - RAJATHI.K; S.SUJA (International Journal of Pharma and Bio Sciences, 2017)
The study was aimed to investigate the molecular mechanisms underlying triggering of apoptosis by quercetin using in silico analysis. The mechanism of binding of quercetin with NF-kB and other apoptotic proteins like BCL2 and BCLXL was analyzed in silico using Schrodinger suite 2009.Quercetin was found to exhibit high-affinity binding resulting from greater intermolecular forces between the ligand and its receptor NF-kB (-0.281 Glide score and -6.172 Docking Score). Quercetin binds to NFÐºB very strongly with metallic coordination.It can act as a inhibitor of apoptosis inhibitor when compared to BCLXL and BCL2.Quercetin down regulates the cell survival proliferative anti-apoptotic proteins thereby can prevent prostate cancer. To confirm this, in vitro study can be carried out with techniques like MTT Assay, Western blot, and polymerase chain reaction.